Recent advances in adaptive and sensory materials and their applications - Conference on Recent Advances in Adaptive and Sensory Materials and Their Applications (1992 : Blacksburg, Virginia); Rogers, Craig A.; Rogers, Robert C. (Lancaster, Pa. : Technomic, 1992)
09